Computer usage and attitudes among Saudi Arabian undergraduate students. (July 2017) - Alothman, Manal; Robertson, Judy; Michaelson, Greg
Abstract: A study of undergraduate students in Saudi Arabia found that although they used technology for an average of 45 h per week and had positive attitudes to it, they did not frequently use technology, in particular computers, in support of their learning. Qualitative evidence suggests that the students were not routinely required to use computers at university, and that in some cases the universities did not provide computing facilities or actively prevented technology usage. Factors which influenced attitudes to computers included: city of study, parental encouragement, and English language proficiency but not gender. Highlights: Students in Saudi Arabia use technology for on average 45 h per week. Students' were positive to learning, but they did not often use it for learning. Computer attitudes were predicted by English proficiency and computing experience. Location and parental encouragement were also predictive factors. No gender differences in computer attitudes were found.